In vitro synthesis of mucin-type O-glycans using saccharide primers comprising GalNAc-Ser and GalNAc-Thr residues. (January 2022) - Sakura, Ryuma; Nagai, Kaori; Yagi, Yuka; Takahashi, Yoshihisa; Ide, Yoshimi; Yagi, Yuki; Yamamoto, Daiki; Mizuno, Mamoru; Sato, Toshinori
Abstract: Mucin-type O -glycosylation of serine or threonine residue in proteins is known to be one of the major post-translational modifications. In this study, two novel alkyl glycosides, N α -lauryl- O -(2-acetamido-2-deoxy-α-d -galactopyranosyl)-l -serineamide (GalNAc-Ser-C12) and N α -lauryl- O -(2-acetamido-2-deoxy-α-d -galactopyranosyl)-l -threonineamide (GalNAc-Thr-C12) were synthesized as saccharide primers to prime mucin-type O -glycan biosynthesis in cells. Upon incubating human gastric cancer MKN45 cells with the saccharide primers, 22 glycosylated products were obtained, and their structures were analyzed using liquid chromatography-mass spectrometry and enzyme digestion. The amounts of glycosylated products were dependent on the amino acid residues in the saccharide primers. For example, in vitro synthesis of T antigen (Galβ1-3GalNAc), fucosyl-T (Fucα1-2Galβ1-3GalNAc), and sialyl-T (NeuAcα2-3Galβ1-3GalNAc) preferred a serine residue, whereas sialyl-Tn (NeuAcα2-6GalNAc) preferred a threonine residue. Furthermore, the glycosylated products derived from GalNAc-Ser/Thr-C12 and Gal-GalNAc-Ser/Thr-C12 using cell-free synthesis showed the same amino acid selectivity as those in the cell experiments. These results indicate that glycosyltransferases involved in the biosynthesis of mucin-type O -glycans distinguish amino acid residues conjugated to GalNAc. The saccharide primers developed in this study might be useful for comparing mucin-type oligosaccharides in cells and constructing oligosaccharide libraries to study cell function. Graphical abstract: Image 1 Highlights: Two novel saccharide primers, GalNAc-Ser-C12 and GalNAc-Thr-C12, were synthesized. O -glycan-type oligosaccharides were obtained by in vitro synthesis using the saccharide primers. Amino acid selectivity in cellular synthesis of mucin-type O -glycans were observed using the saccharide primers.